Allosteric modulation of ghrelin receptor signaling by lipids - Marjorie Damian (Nature Portfolio, 2021)
The membrane is an integral component of the G protein-coupled receptor signaling machinery. Here authors demonstrate that lipids regulate the signaling efficacy and selectivity of the ghrelin receptor GHSR through specific interactions and bulk effects and observe PIP2 and GM3 induced shifts of the conformational equilibrium of GHSR away from its inactive state.